DETERMINATION OF THE RELATIONSHIP BETWEEN EMPATHIC SKILLS AND BURNOUT LEVELS OF NURSES WORKING IN A CITY HOSPITAL - Bakırhan, Derya Şimşekli; İrtegün, Sinan; Yüksekol, Özlem Doğan (Rojan GÜMÜŞ, 2021)
Abstract: Empathy is a process which helps a person to understand the feelings, thoughts and emotions of the other person by putting oneself in that person’s shoes. Nursing is a profession that requires emphatic skills in which communication between people is important in patient care. Not being able to approach the patient and the patient family with empathy, not being able to understand others can create a perception of providing incomplete service and is one of the causes of burnout in nurses. Burnout is important as it may cause anorexia, insomnia and lack of motivation individually in nurses, and also a decrease in the quality of nursing services. The aim of this study is to examine the association between nurses’ empathic skills and their burnout levels. The study was conducted with 289 nurses working in Elazığ Fethi Sekin City Hospital between July and September2020. The data were collected by using a questionnaire form prepared by the researchers, Empathic Skills Scale B-Form and Maslach Burnout Inventory. The study was designed as a correlational study to find out the association between nurses’ empathic skill levels and burnout levels. Mean age of the nurses in the study was 35.83±9.72. Mean working time in the profession was 12.57±9.7 years. Total mean score of nurses from Empathic Skills Scale was 138.93±18.11, while their mean scores from Masclach Burnout Inventory were 22.8±7.2 in emotional exhaustion subscale, 9.1±4.2 in depersonalization subscale and 20.0±6.3 in personal accomplishment subscale. Statistically significant difference was found between empathic skills scale and depersonalization subscale (p0.05). Negative association was found between empathic skills scale and depersonalization subscale. As the empathic scale scores increase, depersonalization subscale scores decrease.
Keywords: Nursing; Hemşirelik